CHANGES IN LAND COVER AND RELATIONS WITH THE EQUATION UNIVERSAL SOIL LOSSES IN BASIN OF THE WESTERN PLATEAU OF SAO PAULO IN BRAZIL (Journal of Geography and Environmental Management, 2023)
The soil loss has become a problem of environmental degradation in Southeastern Brazil. In a region of tropical climate, with precipitations concentrated in summer and sandy soils, the substitution of native vegetation by pasture and cultivation of sugarcane caused changes in the hydrological regime of the hydrographic basins. Soil degradation conditions, with marks present in the landscape, need to be quantified by empirical methods. In the estimates of water erosion, the most used method is the Universal Equation of Soil Losses. The method of estimating soil losses by generating geographic information and spatial data. The Confusion Stream’s basin is located in a region with replacement of pasture areas planted by sugarcane crop for fuel production. This research aims to estimate soil losses in a basin from comparative data from 2009 and 2018, derived from analysis of CBERS satellite images, with spatial resolution of 20 meters, in the mapping of land cover, through the classification of images in the IDRISI geographic information system. Rainfall erosivity factors and soil erodibility were obtained from secondary sources. The topographic factor was obtained from the processing of data from the Shuttle Radar Topography Mission. The areas of the land cover classes were related to factor C of the USLE and data estimates of secondary sources of erosivity factor (R), erodibility factor (K) and topographic factor with the data of slope (LS). From these parameters, an estimate of soil loss was presented for the basin of Confusion’s Stream. The soil loss in the basin of Confusion’s Stream was estimated by 2018 data at 2,484 t/ha/y.
Keywords: erosion, basin Confusion’s stream, agricultural crop.